2022
DOI: 10.3390/microorganisms10112169
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Gut Microbiome Associated with Enterolignan Production

Abstract: Dietary plant lignans are converted inside the gut to enterolignans enterodiol (ED) and enterolactone (EL), which have several biological functions, and health benefits. In this study, we characterized the gut microbiome composition associated with enterolignan production using data from a cross−sectional study in the Japanese population. We identified enterolignan producers by measuring ED and EL levels in subject’s serum using liquid chromatography−tandem mass spectrometry. Enterolignan producers show more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…It appears that while additional lignan sources to the diet do increase serum and urinary enterolactone levels, the ability to produce enterolactone is either impeded or accelerated based on individual microbial diversity. For example, members of the genus Klebsiella are more abundant in both non-enterolactone producers [ 7 ] and individuals with hypertension [ 67 ]. Conversely, both Sawane et al and Lampe et al observed a more robust abundance of the Ruminococcaceae genera (Firmicutes phylum) in enterolactone producers, regardless of dietary intervention [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that while additional lignan sources to the diet do increase serum and urinary enterolactone levels, the ability to produce enterolactone is either impeded or accelerated based on individual microbial diversity. For example, members of the genus Klebsiella are more abundant in both non-enterolactone producers [ 7 ] and individuals with hypertension [ 67 ]. Conversely, both Sawane et al and Lampe et al observed a more robust abundance of the Ruminococcaceae genera (Firmicutes phylum) in enterolactone producers, regardless of dietary intervention [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, members of the genus Klebsiella are more abundant in both non-enterolactone producers [ 7 ] and individuals with hypertension [ 67 ]. Conversely, both Sawane et al and Lampe et al observed a more robust abundance of the Ruminococcaceae genera (Firmicutes phylum) in enterolactone producers, regardless of dietary intervention [ 6 , 7 ]. Thus, greater urinary enterolactone levels are not only a reflection of dietary lignan intake, but are a reflection of host gut microbial diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 In recent years, some cohort studies have used random forest classifications to illustrate the predictive contribution and discriminatory ability of explanatory variables (such as microbial metabolites) to target variables (such as disease-related factors). 36 , 37 Based on random forest machine learning, we constructed a model to distinguish COPD patients from healthy individuals by combining data from fifteen intestinal microbiotas at the genus level. According to the ROC results, our classification model achieved good results in discriminating patients with COPD from healthy participants, suggesting that intestinal microbiota can effectively distinguish COPD patients from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…END-2 and Lactonifactor longoviformis strains have been shown to catalyze this oxidation reaction. [14][15][16] Although strains isolated from gut microbiota were able to transform SDG into END and ENL, most of them are not currently approved for food production, which limits their application in foods. 11 Lactic acid bacteria with ⊎-glucosidase activity were found for applications in winemaking, sourdough making as aromatic starters, and bioconversion of SDG, ginsenosides and isoflavone.…”
Section: Introductionmentioning
confidence: 99%